Contextual Learning Strategies in Improving Students Understanding of Islamic Values - Amril Huda M; Andra Andra; Krim Ulwi (Yayasan Adra Karima Hubbi, 2025)
Background. Contextual Teaching and Learning strategies are an effective approach to improve students